Area Development Programmes Central Region Uttar Pradesh - Planning Commission (Planning Commission, 1973)
The central Region of Uttar Pradesh is one of the five economic regions into which the State has been divided on the basis of contiguity, similar geographical and climatic conditions, pattern of economic activity, density of population and agricultural pattern. the classification of regions has been made with the objective of giving a regional orientation to the process of planning and development in order to ensure balanced regional development with due regard to various spatial characteristics. the Central region comprises 9 districts viz. Sitapur, Khori, Hardoi, Kanpur, Unnao, Fatehpur, Rae-Bareli and Barabanki.
Planning Department, Uttar Pradesh